Peranan cash internal controlling dalam menunjang cash management effectivity - Herlina Herlina (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2019)
This study aims to determine the adequacy of the internal control of cash in Perusahaan SMG. The method of observation and data collection techniques was used questionnaires, and interviews. The descriptive method was used in this study. Based on the results of internal control conducted by Perusahaan SMG has been adequate, it is supported by elements of the control environment, risk assessment, control activities, information and communication, and monitoring. The cash management applied by Perusahaan SMG has been effective this is reflected in their procedures for cash receipts, petty cash receipts, cash disbursements, and a small cash outlay. Finally, it can be concluded that the internal control of cash has been instrumental in supporting the effectiveness of cash management.